Hybrid state approach for modelling electrical and mechanical systems - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
Many engineering systems contain discrete components or decision makers as well as continuous dynamical components. The variables in these systems can be quantitatively represented by discrete and continuous states. These states affect each other in the system. These types of complex systems can be modelled by hybrid state systems. In this study, a hybrid state approach is presented to model electrical and mechanical systems. Two representative examples, which can not be directly modelled by the nonlinear system approach, are provided to demonstrate the effectiveness of the hybrid state approach in modelling. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: hybrid systems; discrete and continuous systems; modelling